Bone Maturation in Patients with Angle’s Class II Division 1 Malocclusion Caused by Dental Development - Clotilde de la Caridad Mora Pérez; Rasiel Cruz Caballero; Saray Martínez Santos; Gretel Rivas Pérez (Medisur)
Background: chronological age does not always allow assessing the somatic development and maturation of patients. Therefore, we resort to bone maturation study, a safer and more reliable method to assess the biological age of individuals. Objective: To determine bone maturation from dental development in patients with Angle’s class II division 1 malocclusion. Methods: A descriptive, observational and cross-sectional study was conducted at Area II in Cienfuegos. It included 50 children. The study of bone age of patients with class II division 1 with orthodontic treatment was performed through assessment methods of bone maturation in calcification stages of the seven left mandibular teeth, using the Demirjians maturation scale. Results: We found that, generally, bone age increased in relation to decimal, dental and chronological ages in both sexes, mainly in males. It was found that there is a strong correlation between chronological and decimal ages; the correlation between bone age, chronological age and decimal age is lower. Conclusions: The Demirjians method could be used in both sexes to determine bone age in patients under orthodontic treatment; values increased mainly in males.